KONSEP FEMINISME GAYATRI CHAKRASVORTY SPIVAK DAN UPAYA MEMBANGUN KELUARGA UNGGUL (KAJIAN FEMINISME MODERN) - Dewi Yunairi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
Concept understanding is very necessary in various things as well as understanding about balancing roles in a family, it needs the understanding of feminism concept. The concept which initiated by Gayatri Chakrasvorty Spivak becomes a reference, as the identity of women in post-colonial feminism is understood as an awareness of women's differences. Third world women are considered to have a greater burden of oppression than first world women. The burden is based on colonial and imperial oppression of gender, race, ethnicity and religion, so that women's identity in postcolonial feminism is directed at a more productive domain to understand identity based on nationality awareness. Gayatri Chakrasvorty Spivak as one of the postcolonial theorists carefully sees that sexual oppression directed at third world women is an oppression that leads to subaltern sovereignty. Therefore, a transformation of subaltern women's awareness is needed by understanding the differences in women's experiences as the basis that woman empowerment is important to be able to form women who are more active and productive, and contribute positively to their families and communities. Overcoming subaltern in families who have a patriarchal tradition is certainly not easy, many things and efforts must be carried out. Providing space and opportunities for women is one of the efforts to uphold justice for women to take roles. Efforts to make a superior family can not be separated from the role of women. The existence of cooperation between parts of the family becomes the perfection and excellence of a family.